2011
DOI: 10.1177/0194599810392655
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Esophageal Bolus Impaction

Abstract: There was a significant seasonal variation in the incidence of acute esophageal bolus impaction. This variation was pronounced in patients with a coexisting atopic diathesis but was nonsignificant in patients without atopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 15 publications
1
19
0
2
Order By: Relevance
“…Similar results have been demonstrated with 330 cases of EoE reported in four additional studies with increase in the diagnosis of EoE in pollen seasons 68-71 . Furthermore, Larson in a series of 313 esophageal bolus impactions found an increase in cases in the summer and fall 72 . However, Sorsen and colleagues evaluation of 753 endoscopies in adults with 44 patients having EoE did not find any seasonality to the diagnosis.…”
Section: The Role Of Aeroallergens In Eoementioning
confidence: 99%
“…Similar results have been demonstrated with 330 cases of EoE reported in four additional studies with increase in the diagnosis of EoE in pollen seasons 68-71 . Furthermore, Larson in a series of 313 esophageal bolus impactions found an increase in cases in the summer and fall 72 . However, Sorsen and colleagues evaluation of 753 endoscopies in adults with 44 patients having EoE did not find any seasonality to the diagnosis.…”
Section: The Role Of Aeroallergens In Eoementioning
confidence: 99%
“…Several studies have found changing clinical symptoms during peak pollen seasons, especially in those with concomitant allergic rhinitis. 810 The frequency of diagnosis also appears to increase during pollen seasons, with a lower frequency found in winter. 1114 However, other studies have found no clear link among aeroallergen sensitization, symptom onset, and seasonal diagnosis of EoE.…”
Section: Introductionmentioning
confidence: 99%
“…La incidencia fue 33 casos/100,000 habitantes y año. Esta cifra es significativamente mayor que la publicada en la literatura, donde la incidencia estimada es de 13 a 20 casos/100,000 habitantes y año 9,10 . De hecho, se ha observado que el área geográfica tiene influencia sobre los CE y más concretamente sobre la impactación por bolo alimenticio 9,11 .…”
Section: Discussionunclassified